The Influence of Product Quality, Brand Image, and Brand Trust on Automatic Motorcycle Purchase Decisions - Hawa, Sarah Dien; Suroso, Agus (Research Horizon, 2025)
Amid increasing competition in the Indonesian motorcycle market, understanding the factors that influence consumers’ purchasing decisions is crucial for manufacturers. This study investigates the extent to which product quality, brand image, and brand trust shape consumers’ purchasing decisions for automatic motorcycles. Employing a quantitative descriptive design, data were collected from 170 automatic motorcycle users selected through purposive sampling, and hypotheses were tested using multiple linear regression. The findings indicate that product quality does not exert a significant influence on purchase decisions, whereas brand image and brand trust have positive and significant effects. Additionally, product quality, brand image, and brand trust collectively exert a significant simultaneous effect on consumers’ decisions to purchase automatic motorcycles. This study contributes to marketing literature by providing empirical evidence on the relative importance of brand-related factors in influencing consumer behavior and offers practical insights for enhancing marketing strategies.